PENGARUH LATIHAN DEPTH JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMPN 1 MANDAU - Heriyandi, Tri; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
The problem in this research is that when striking the ball it seems less like jumping. And when jumping is often not optimal due to weak leg muscle strength, the opponents are easily looking for points when the conditions in the Male Volleyball Team 1 are Mandau. The title of this research is "The effect of depth training on leg muscle power on the male volleyball team in SMPN 1 Mandau" so that the future goals of athletes after research can perform much better and above all and discover whether there is an increase in power power of the athlete in volleyball to keep track of the opponent's game and to achieve maximum results in the future. The form of this research is (with a pretest-post-test design approach of one group) with a population of the Mandau 1 Junior High School team. The data in this study are the entire population of 10 people. The instrument used in this research was to use a vertical jump test, which aims to determine the effect of deep jump training on leg muscle strength on men's volleyball team at SMPN 1 Mandau. The data is then statistically processed to test the normality with the help of the lilifours test at a significant level of 0.05 ?. The hypothesis is that there is an effect of Deep Jump Training on leg muscle strength in the men's volleyball team at SMPN 1 Mandau. Based on the analysis of the normality of the data X, it produces an Lcount of 0.181 and an Ltable of 0.271, which means that the Lcount <Ltable. while the Y-variable yields Lcount of 0.238 and Ltable of 0.271. This means Lcount < LTable. Based on the analysis of statistical data, there is an average variable X 12.83 and an average variable Y of 10.42, after which the data is normally distributed. Thus it can be concluded that for the effect of the variable x with the obtained variable y the value of t = 2,466 and tcount> ttable (5,714)> (1,833), then Ha is accepted, in other words, there is a significant influence on exercising the influence of the Deep Jump exercise on power leg muscles in the men's volleyball team in SMPN 1 Mandau.Key Words: Depth Jump Exercise, Leg Muscle Power